The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1021/acs.joc.5b02475
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Pd–Imidate Complexes: Broadly Applicable Catalysts for the Synthesis of Chemically Modified Nucleosides via Pd-Catalyzed Cross-Coupling

Abstract: A broadly applicable catalyst system consisting of water-soluble Pd--imidate complexes has been enployed for the Suzuki-Miyaura cross-coupling of four different nucleosides in water under mild conditions. The efficient nature of the catalyst system also allowed its application in developing a microwave-assisted protocol with the purpose of expediting the catalytic reaction. Preliminary mechanistic studies, assisted by catalyst poison tests and stoichiometric tests performed using an electrospray ionization spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 110 publications
0
28
0
Order By: Relevance
“…In a collaborative effort with the Serrano group, PTA based palladium complexes were synthesized and screened for the catalytic cross-coupling of nucleoside in water. In this study, the first set of [Pd(imidate) 2 (PTA) 2 ] were synthesized and found to exhibit appreciable water-solubility (110 mg/mL) [37,51]. The titled complexes can be easily synthesized by the reaction between trans-[Pd(imidate) 2 (SMe 2 ) 2 ] and PTA ligand.…”
Section: Suzuki-miyaura Cross-coupling Using Catmentioning
confidence: 99%
See 1 more Smart Citation
“…In a collaborative effort with the Serrano group, PTA based palladium complexes were synthesized and screened for the catalytic cross-coupling of nucleoside in water. In this study, the first set of [Pd(imidate) 2 (PTA) 2 ] were synthesized and found to exhibit appreciable water-solubility (110 mg/mL) [37,51]. The titled complexes can be easily synthesized by the reaction between trans-[Pd(imidate) 2 (SMe 2 ) 2 ] and PTA ligand.…”
Section: Suzuki-miyaura Cross-coupling Using Catmentioning
confidence: 99%
“…Initial studies were directed toward the development of an efficient protocol for the Heck coupling of 5-iodo nucleoside using the Pd-dba catalyst [35]. Next, in order to have an efficient water-soluble catalytic system, we developed Pd-imidate based complexes in collaboration with the Serrano group, which were successfully utilized for Heck and Suzuki-Miyaura cross-coupling reactions [36][37][38]. Subsequently, we also developed triazaphosphaadamantane (PTA) based water-soluble phosphines, which are used in combination with palladium acetate for C-C and C-heteroatom bond forming reactions [39][40][41][42][43].…”
Section: Introductionmentioning
confidence: 99%
“…Our research group has over the years developed more efficient palladium-based catalytic systems involving caged phosphine ligands such as triazaphosphaadamantane (PTA) and its derivatives (PTABS and PTAPS). 30 These ligand systems either as complexes of palladium (e.g., PTA complexes such as [Pd(Sacc) 2 (PTA) 2 ] Cat 2 or [Pd(Mal) 2 (PTA) 2 ] Cat 3 shown in Figure 1) [31][32][33] or in situ activation with a palladium precursor [PTABS with Pd(OAc) 2 ] 34 have been effective in catalyzing the modification of nucleosides (Suzuki-Miyaura, Heck alkenylation, Sonogashira coupling, aminocarbonylation) 30,35 as well as the functionalization of chloroheteroarenes (amination, etherification, and thioetherification). [36][37][38] In 2015, utilization of [Pd(Sacc) 2 (PTA) 2 ] catalytic system in catalyzing the Heck alkenylation at 1.0 mol% concentration for 5′-O-DMTr-5-iodo-2′-deoxyuridine failed…”
Section: Figure 1 Catalytic Systems Used For Cross-coupling Reactionsmentioning
confidence: 99%
“…Thus, excess use of boronic acid is needed to direct the reaction toward completion [78]. Likewise, a water-soluble Pd-imidate complex has been utilized for the Suzuki-Miyaura cross-coupling of four different nucleosides with (hetero)arylboronic acids under microwave-assisted protocol [79]. Sodium tetraphenylborate was efficiently employed instead of ArB(OH) 2 , ArB(OR) 2 , or ArBF 3 K in the cross-coupling reaction with four-fold of aryl bromides in the presence of different palladium catalysts under microwave heating, yielding a variety of biaryl derivatives [80,81].…”
Section: Suzuki Cross-coupling Reactionmentioning
confidence: 99%